Repertorio de la Legislación social y educativa entre 1822 y 1938 y su incidencia en la enseñanza de las personas ciegas - Burgos Bordonau, Esther (Cuadernos de Historia del Derecho, 2007)
The article pretends an approachment to the social and educative situation that amongst the whole 19th century and the first quarter of the 20th, had the blind people. We locate our laws, rules and decrees compilation in a historical frame that permits a better understanding not only of the nation’s situation in certain moments of its history but also the influence that this social and political changes had within the disabled people.